DIGITAL IMPRESSIONS VERSUS TRADITIONAL IMPRESSIONS: AN OVERVIEW - Marius Negucioiu; Smaranda Buduru; Diana Coman; Ana-Maria Condor; Antonela Berar; Daniela Condor; Rareș Buduru; Andreea Kui (Romanian Journal of Oral Rehabilitation)
Aim of the study This study aimed to evaluate the time efficiency and accuracy of digital scanning compared to traditional impression methods in dentistry, as well as their impact on patient comfort and satisfaction. Materials and methods Bibliographic searches were conducted in databases (PubMed, Scopus, Web of Science), applying relevant keywords to identify studies comparing digital and conventional impression techniques in dentistry. The data was extracted and graphically represented. Results Data from clinical studies indicated mixed conclusions regarding accuracy and impression parameters. Time spent on impressions seems to be less for digital techniques, but results are conflicting. Patients reported increased comfort and a clear preference for digital scans due to their less invasive nature and reduced discomfort. Conclusions Integrating digital scanning technology into modern dental practices offers significant benefits in terms of procedural efficiency and patient satisfaction, while accuracy and time depend by circumstances such as edentulism type and length of scan.